Can Stephen Colbert Bring Back Stephen Colbert? Alternate, Fictional Personas in Copyright - Shaffy, Kourosh (The Columbia Journal of Law & the Arts, 2018)
This Note argues that Stephen Colbert should have the right to use his former Comedy Central persona on his new CBS show. Creator-performers of characters that are fictionalized versions of their own, real personas should not lose their rights to these characters because of copyright law. Traditional concerns associated with a need for copyright (for example, the danger of unapproved copying) are not present where the author’s presence is essential to performance of the character, as is certainly the case here. Nobody can play the fictional Stephen Colbert character but the real Colbert. An artist like Colbert must be free to use his character.